2020
DOI: 10.3390/jcs4040145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structural Parameters on the Deformational Behaviors of Multiply 3D Layer-by-Layer Angle-Interlock Para-Aramid Fabric for Fiber-Reinforcement Composite

Abstract: Materials used in the technical application including composite reinforcements and ballistic fabrics should show not only good mechanical performance but also better deformational behaviors. Meanwhile, three dimensional (3D) warp interlock fabrics have been widely employed in such applications to substitute the two dimensional (2D) fabrics because of their enhanced through-the-thickness performance and excellent formability. The deformational behaviors of such 3D warp interlock fabrics have been also influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…As shown in Fig. 1c, d, there have three yarn systems of 3D fabric absorbers: warp (x), weft (y), and binding warp (z) [25]. The x and y directions are arranged straight and parallel, and the z direction yarns are interwoven to join the four layers into a single unit, giving the fabric extremely high fracture toughness, fracture toughness and impact damage tolerance [26].…”
Section: The Structure Of 3d Fabric Absorbersmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 1c, d, there have three yarn systems of 3D fabric absorbers: warp (x), weft (y), and binding warp (z) [25]. The x and y directions are arranged straight and parallel, and the z direction yarns are interwoven to join the four layers into a single unit, giving the fabric extremely high fracture toughness, fracture toughness and impact damage tolerance [26].…”
Section: The Structure Of 3d Fabric Absorbersmentioning
confidence: 99%
“…To overcome the above structural weakness of the common 2D MA fabrics, numbers of 3D woven fabrics have been reported that are structurally strong and lightweight [24][25][26] and can serve as the enhanced MA absorbers due to the established 3D microwave absorbing networks within those fabrics [27,28]. For instance, Zhang et al fabricated a series of 3D gradient honeycomb woven composites (3D GHWC) with the basalt and carbon fibers as reinforcement and the carbon black-carbonyl iron powder-modified epoxy as the resin matrix.…”
Section: Introductionmentioning
confidence: 99%
“…However, it does not come close to the ballistic protection offered by the aramid fibers, threads, and fabrics in personal armor. Another advantage of ultra-fine polymer filaments (not just aramid [13,61,62]) is that they offer an incredibly flexible material, which supports a high level of comfort for the wearer. To make it easier to understand, see Figure 1.…”
Section: State Of the Artmentioning
confidence: 99%
“…Apart from the commonly used 2D and UD textile structures, 3D woven fabrics are becoming a promising ballistic textile structure due to their excellent moulding ability [ 36 , 37 , 38 , 39 , 40 ] and ballistic protection performance [ 41 , 42 ]. The 3D woven fabric’s structure could be involved not only in planer but also nonplanar body armour systems considering various structural parameters to give better ballistic protection and comfort to the wearer [ 43 ].…”
Section: Introductionmentioning
confidence: 99%